Clinical pathways of breast cancer patients treated in the Federal District, Brazil - Barros, Angela Ferreira [UNESP]; Araujo, Jeniffer Melo de; Murta-Nascimento, Cristiane [UNESP]; Dias, Adriano [UNESP] (Revista De Saude Publica, 2019)
OBJECTIVE: To identify the clinical pathways of women with breast cancer treated in public hospitals, and to analyze the factors that influence the time interval between the first appointment and the start of therapy. METHODS: A cross-sectional study was conducted with 600 women with breast cancer treated in nine public hospitals in the Brazilian Federal District. Patients were interviewed between September 2012 and September 2014. Simple and multiple logistic regression models were adjusted to evaluate the variables associated with the time interval studied. The most frequent pathway was the one that started in primary care with following care in the therapy service (28.9%). In the multiple adjustment, factors associated to a longer time interval between the first appointment and therapy were: lower family income (OR = 1.89; 95% CI 1.32-2.68), the first appointment in public services (OR = 1.78; 95% CI 1.20-2.64), care in more than two health services in the clinical pathway (OR = 1.71; 95% CI 1.19-2.44); and obtaining the anatomopathological analysis of the biopsy in public services instead of private health services (OR = 1.87; 95% CI 1.29-2.71). Independently, the implementation of specialist appointment scheduling, with care regulation, was associated with a shorter time interval between first appointment and therapy (OR = 0.33; 95% CI 0.16-0.65). CONCLUSIONS: We observed that multiple pathways were covered by women with breast cancer treated in public services of the Federal District. Socioeconomic iniquities and several aspectos of the pathways covered were associated with a longer time interval between the first appointment and the start of breast cancer therapy.
Keywords: Breast Neoplasms, therapy; Time-to-Treatment; Health Care Quality, Access, and Evaluation; Health Status Disparities; Health Services Accessibility